Cultural Values Study of SITARO Society's Motto “Pakatiti Tuhema, Pakanandu Mangena, Boleng Balang Singkahindo” (As a Contribution for Culture Learning in Education) - Devilito Prasetyo Tatipang; Ceisy Nita Wuntu; Aprillya A. Suoth; Triesye A. Laloan (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The form of culture as a system of ideas is very abstract, cannot be touched or photographed and is contained in the minds of individuals who adhere to that culture. One form of culture in the SITARO community is a reflection of the SITARO community's motto, namely "Pakatiti Tuhema, Pakanandu Mangena, Boleng Balang Singkahindo". Considering the importance of knowing the cultural values of the SITARO community through their motto, as well as the lack of research discussing these cultural values, the purpose of this study is to analyze the cultural values contained in the SITARO community's motto. In this study, the researcher used a qualitative method. In addition, the data collection process used a semi-structured interview technique with additional data from observations and literature studies, so as to get more detailed results from the problems raised. The results of the analysis show that the motto of the SITARO community is the basis of every activity they do both in the family and community environment. This reflection of SITARO's motto produces a very large positive impact in people's lives which then creates an environment that is mutually helpful, supportive and focused on a common goal. In addition, in the future, it is hoped that further researchers will be able to study more deeply about the cultures that exist in SITARO, as well as research that can contribute to cultural learning in Indonesia, especially in North Sulawesi Province.